Evaluation of the Elderly Protection Program (PAITUA) for Improving Elderly Welfare in Southwest Papua Province - Novalius Abraham Bleskadite; Sapto Pramono; Ika Devy Pramudiana (NAAFI: JURNAL ILMIAH MAHASISWA, 2024)
The Elderly Protection Program – Program Perlindungan Hari Tua (PAITUA) was launched in Southwest Papua Province in 2023 to improve the welfare of the elderly, particularly those in rural and economically vulnerable areas. This qualitative evaluation study assesses the effectiveness of PAITUA in addressing the basic needs of the elderly, including food, healthcare, and daily necessities, using William N. Dunn’s six evaluation indicators, which include effectiveness, efficiency, adequacy, equity, responsiveness, and accuracy. The study finds that the monthly financial assistance of Rp250,00 has positively impacted elderly welfare, though it remains inadequate for more complex needs, especially healthcare. While the program’s distribution through bank accounts ensures transparency and efficiency, challenges related to financial literacy and limited banking access in remote regions persist. The equity of the program has improved, but geographical barriers continue to hinder full coverage, particularly in mountainous and isolated areas. Furthermore, the program’s responsiveness to the needs of elderly individuals and their families has been commendable, though healthcare services and more comprehensive support are required. Administrative barriers, such as missing identification documents, have led to exclusions from the program, highlighting the need for simplified registration processes. This study recommends increasing the assistance amount, improving infrastructure and accessibility in remote areas, and addressing administrative challenges to make PAITUA a more comprehensive and sustainable solution for improving elderly welfare in Southwest Papua.